Congenital protein C deficiency and thrombotic disease in nine French families. Issue 6454 (10th November 1984) - Horellou, M H; Conard, J; Bertina, R M; Samama, M
Abstract : Investigation of 118 patients for protein C deficiency using an immunological and a functional assay, and subsequent investigation of those (nine) found to be deficient, identified 22 patients (14 women, eight men) with protein C deficiency, of whom six were asymptomatic, 15 had histories of venous thromboembolism, and one had a history of arterial thromboembolism. Protein C deficiency was associated in the nine probands with young age at first episode of thromboembolic disease (mean 24.1 (SD 11.9) years), absence of a precipitating condition (five (56%], and a family history of thromboembolic disease (six (66%]. Investigation of the nine families suggested autosomal dominant transmission of the defect. Thromboembolic episodes were seen in patients with protein C antigen concentrations below 0.6 U/ml. Mean (SD) protein C antigen concentrations were 0.48 (0.12) U/ml in 18 patients not receiving oral anticoagulant treatment and 0.28 (0.05) U/ml in four receiving such treatment. One patient with severe protein C deficiency (0.16 U/ml) developed skin necrosis soon after starting oral anticoagulant treatment.